From depression to wellbeing: How to protect the mental health of isolated people under the “dynamic clearance” of patients with COVID-19 - Bai, Yuntao; Ma, Shuai (Frontiers in Psychology, 2023)
In 2020, COVID-19 became a global pandemic. The Chinese government's quarantine measures tend to cause anxiety, tension and depression among the quarantined people. Differential game is used to analyze the above problems. Considering that the government and social forces can actively guide the local people to alleviate the above psychological problems, this article constructs a differential game model of self-regulation, government guidance and social forces guidance. Then, the psychological benefits of the masses and the benefits of the whole society under the three modes are obtained, and the applicable conditions of various connection modes are compared. The research results show that: compared with social power channeling, the public under the government channeling mode can obtain more psychological benefits. However, with the increase of guidance, the difference between the psychological benefits of different ways of guidance first decreases and then tends to be stable. Under the guidance mode, the social benefits of the government decrease, and the more guidance, the smaller the social benefits.